2021
DOI: 10.3390/jcm10215052
|View full text |Cite
|
Sign up to set email alerts
|

Lockdown Effect on Elderly Nutritional Health

Abstract: Pandemics and lockdowns may be associated with unpremeditated consequences, such as bodyweight changes, isolation, as well as sedentarity. Reports have been published on malnutrition among patients suffering from COVID-19. This study aimed to highlight the short-term effects of the lockdown on the nutritional health of elderly people living at home and benefiting from home care services, yet without any COVID-19 pathology. In 50 subjects displaying weight, body mass index, and MNA score stability two months ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 10 publications
3
5
0
Order By: Relevance
“…In line with previous studies on older adults who are institutionalized or living at home, our patients exhibited significant worsening of nutritional status after discontinuation of daycare services [ 48 , 49 ]. Malnutrition among the elderly is a vicious cycle, even in individuals not suffering directly from COVID-19, as it is associated with weight loss and fragility, which in turn worsen a person’s health status.…”
Section: Discussionsupporting
confidence: 90%
“…In line with previous studies on older adults who are institutionalized or living at home, our patients exhibited significant worsening of nutritional status after discontinuation of daycare services [ 48 , 49 ]. Malnutrition among the elderly is a vicious cycle, even in individuals not suffering directly from COVID-19, as it is associated with weight loss and fragility, which in turn worsen a person’s health status.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, older adults are prone to developing frailty due to vulnerability to environmental stressors [ 9 , 10 ] such as a pandemic with mandated lockdown strategies that reduce physical contact with others and restrictions on shopping and travel. We found that nutrition risk was similar to other studies of the Canadian population [ 1 ] and was stable over the 3 months of the study, unlike Ghanem et al [ 38 ], who reported that malnutrition approximately doubled in prevalence during a one-month lockdown in France in March–April 2020. However, the population in that study was older, more frail and also had home care support suspended for that month, which likely exacerbated their decline in nutrition [ 38 ].…”
Section: Discussionsupporting
confidence: 89%
“…We found that nutrition risk was similar to other studies of the Canadian population [ 1 ] and was stable over the 3 months of the study, unlike Ghanem et al [ 38 ], who reported that malnutrition approximately doubled in prevalence during a one-month lockdown in France in March–April 2020. However, the population in that study was older, more frail and also had home care support suspended for that month, which likely exacerbated their decline in nutrition [ 38 ]. On the other hand, we did not have pre-pandemic information on the nutrition risk of our study group.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Thus, it is possible to predict that social distancing will be associated with weight gain or deterioration of metabolic markers such as blood sugar and lipid profiles. Several studies report significant weight gain or worsening of cardiometabolic parameters during the COVID-19 pandemic (12)(13)(14)(15), while a few report a contrary result (16) or both results (17,18). Previous studies report controversial results because they were based on short-term follow-up data, mostly from questionnaires, leading to inadequate information on which to base an assessment of fundamental weight changes and related parameters after lockdown.…”
Section: Introductionmentioning
confidence: 99%